Randomized clinical trial of cutting balloon angioplasty versus high-pressure balloon angioplasty in hemodialysis arteriovenous fistula stenoses resistant to conventional balloon angioplasty - Aftab, S.A. (2016)
10.1016/j.jvir.2013.10.020